Physical Therapy Rehabilitation Approach for Phase II CHF Due to RHD Post-MVR: A Case Study - Fera Syofwatin Ni’mah; Farid Rahman; Kadek Agustini Aryani (Gaster, 2026)
Introduction: Congestive Heart Failure (CHF) due to Rheumatic Heart Disease (RHD) often causes cardiac dysfunction after mitral valve replacement (MVR) and tricuspid valve repair (TVR) surgery. Phase II cardiac rehabilitation is important to improve aerobic capacity, cardiorespiratory function, and quality of life in postoperative patients. Objective: To examine the effects of a phase II physical therapy rehabilitation program on improving aerobic capacity in Class II CHF patients with RHD after MVR and TVR. Method: A single case study of a 43-year-old woman with postoperative CHF FC II, who underwent 13 aerobic exercise sessions consisting of walking on a track, treadmill, and stationary bicycle based on the FITT (Frequency, Intensity, Time, Type) principle. Parameters evaluated included blood pressure, heart rate, oxygen saturation, Borg scale, and distance covered in the Six Minute Walking Test (6MWT). Results: Showed an increase in 6MWT distance from 355 meters to 446 meters, METs from 4.18 to 4.9, and Borg score from 6 to 7 with stable vital signs. Conclusion: Gradual aerobic exercise in phase II rehabilitation is safe and effective in improving aerobic capacity, hemodynamic response, and activity tolerance in patients, while preventing deterioration of condition and readmission.